BERGERAK DAN BERKARYA BERSAMA SLB B-C CAHAYA JAYA, KELAPA GADING - Shanty Sudarji (Universitas Bunda Mulia, 2017)
In Indonesia, education can be classified into formal, non-formal, and informal education. Special School (SLB) is one form of formal school that is devoted to provide educational services for students with special needs. Students and special needs students have significant differences in some important dimensions of their humanitarian function. This explains that physically, psychologically, cognitively, or socially obstructed in achieving its goals or needs and maximum potential, including those who are deaf, blind, have speech impairment, disability, mental retardation, emotional distress. Also gifted children with high intelligence. SLB B-C Cahaya Jaya provides special education for special needs students, including student with hearing impairment dan students with intellectual disabilities. This activity was given for 40 students with special needs which 11 students with hearing impairment and 29 students with intellectual disabilities. The activities are singing, playing balloons, pasting, painting, garnishing and dining. The objective is to refresh physical motor activity and learning to make a simple artwork with practical and fun means. The hoped benefits are to stimulate creativity, increase motor-perception coordination and to train social abilities to interact with others. Students can follow the activities cooperatively, and they can finish them independently or with assistance. Overall of the process, the activities went well.Keywords: hearing impairement, intellectual disability, perception-motor